Types of new one-family houses - Drozg, Vladimir (Journal for Geography, 2013)
The article shows types of one-family houses that appeared in Slovenia in the previous century. Typology of a modern one-family house is based on form, source of provenience and the period in which the houses were first built. The recognized types do not show any regional features, as in the case of a farmhouse. What is more important is the time of appearance that shows values, construction typology and the formation of the living environment.